2009
DOI: 10.1002/art.27230
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis–specific autoantibodies to peptidyl arginine deiminase type 4 inhibit citrullination of fibrinogen

Abstract: Objective. Autoantibodies to citrullinated proteins are specific for rheumatoid arthritis (RA) and recognize epitopes centered by citrulline, a posttranslationally modified form of arginine. Peptidyl arginine deiminase type 4 (PAD-4), the enzyme that converts arginine into citrulline, is in itself a target for RAspecific autoantibodies. This study was undertaken to assess whether anti-PAD-4 autoantibodies interfere with citrullination in vitro in patients with RA, and to identify peptide targets of anti-PAD-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 18 publications
1
38
1
Order By: Relevance
“…Recently, Van Beers et al have shown limited serum reactivity against specific citrullinated epitopes compared to the extended repertoire of citrullinated polypeptides contained in synovial fluid of RA patients, including vimentin and fibrinogen, implying that the formation of in-situ immune complexes might contribute to disease onset [31]. Interestingly, we also included citrullinated PAD-4 peptide, as anti-PAD4 antibodies have been detected in the serum of RA patients before disease onset and have been implicated in disease pathogenesis [16]. An approach based on citrullinated epitopes rather than whole proteins has been selected to achieve optimal reactivity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Van Beers et al have shown limited serum reactivity against specific citrullinated epitopes compared to the extended repertoire of citrullinated polypeptides contained in synovial fluid of RA patients, including vimentin and fibrinogen, implying that the formation of in-situ immune complexes might contribute to disease onset [31]. Interestingly, we also included citrullinated PAD-4 peptide, as anti-PAD4 antibodies have been detected in the serum of RA patients before disease onset and have been implicated in disease pathogenesis [16]. An approach based on citrullinated epitopes rather than whole proteins has been selected to achieve optimal reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Linear citrullinated (Cit) peptides derived from the sequence of human proteins were as follows: PAD 211-30 (VCitVFQATCitGKLSSKCSVVLG) derived from PAD, vim 60-75 (VYATCitSSAVCitLCitSSVP) derived from vimentin, enol [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] (KIHACitEIFDSCitGNPTVE) derived from alpha-enolase, fibrin 617-31 (HSTKCitGHAKSCitPVCitG) derived from the alpha chain of fibrinogen, col-II 358-75 (GACitGLTGCitPGDAGPPGPP) from type II collagen and fillaggrin [SHQEST(Cit)G(Cit)SRGRSGRSG] derived from filaggrin. A non-citrullinated peptide, ctrlPAD (EPLGLQCTFINDFFTYHIRH) derived from PAD was used as control.…”
Section: Synthetic Peptidesmentioning
confidence: 99%
See 3 more Smart Citations